Effect of Return on Assets and Capital Adequacy Ratio on Changes in Stock Prices - Gunardi, Gunardi; Hatimatunnisani, Hani; Azizah, Nur; Kesumah, Priatna; Fauzany, Riffka (PT. Riset Press International, 2026)
This study aims to analyze the effect of Return on Assets (ROA) and Capital Adequacy Ratio (CAR) on stock price changes at Bank Mandiri for the period 2010–2023. The method used is a quantitative approach with a causal associative design. The data used are secondary data in the form of annual financial reports and stock price data obtained from the Indonesia Stock Exchange. The analysis technique used is multiple linear regression, supported by the classical assumption test, t-test, F-test, and coefficient of determination (R²). The results show that partially, ROA has no significant effect on stock price changes, nor does CAR show a significant effect. Simultaneously, ROA and CAR also have no significant effect on stock price changes. The low coefficient of determination indicates that most stock price variations are influenced by factors outside the research model, such as macroeconomic conditions, government policies, and market sentiment. This study's contribution implies that fundamental indicators such as ROA and CAR are not always the primary determinants of stock price movements, particularly in the banking sector. This study also emphasizes the importance of considering external factors and investor psychology in investment analysis. The practical implication is that investors are advised not to rely solely on financial ratios, but also to pay attention to broader market dynamics when making investment decisions.